Peran Sasambo Youth Education Dalam Optimalisasi Kualitas Layanan Pendidikan Di Nusa Tenggara Barat - Fadillah Ahmad Nur; Sunarto Sunarto Sunarto; Umiarso Umiarso Umiarso (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Sasambo Youth Education Nusa Tenggara Barat (SYE NTB) as a youth organization has played an active role in providing services and guidance in various online and offline educational activities from kindergarten-equivalent to higher education. The NTB Provincial Government has actually made efforts and paid attention to education in NTB. However, SYE NTB continues to contribute and take part in overcoming educational problems due to the Covid-19 pandemic which requires changing the learning system. SYE NTB certainly has a strong reason to continue to play a role in education issues in NTB. The purpose of this article is to find out the reasons behind SYE NTB providing educational services and also to find out the various programs held to optimize the quality of education in NTB. The method used in this research is a qualitative research method. The results of this article show that SYE NTB has a vision and mission which then encourages other NTB youths to join SYE in order to achieve the targets and goals that have been proclaimed and realized through various programs.